2020
DOI: 10.1097/md.0000000000022207
|View full text |Cite
|
Sign up to set email alerts
|

Observation for the effect of rTMS combined with magnetic stimulation at Neiguan (PC6) and Sanyinjiao (SP6) points on limb function after stroke

Abstract: Background: Stroke is the primary cause of adult disability in China, which causes serious personal, family, and social burden. “Central peripheral central” closed-loop rehabilitation theory is proved to be an effective neural rehabilitation model. Based on this theory, repetitive transcranial magnetic stimulation (rTMS) combined with magnetic stimulation of Neiguan (PC6) and Sanyinjiao (SP6) may be an effective treatment for limb dysfunction after stroke. However, the efficacy and mechanism of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…In contrast, the storage level of energy and metabolites of the brain itself is shallow, which means that the brain is vulnerable to blood flow interference [ 18 ]. Some studies have found that acupuncture for early stroke (12–24 h) can promote the expression of vascular endothelial growth factor (VEGF), which helps to restore oxygen or nutrition supply in the ischemic penumbra [ 19 ]. Acupuncture also provides a beneficial environment for injured tissue, providing a theoretical basis for acupuncture intervention in early stroke [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the storage level of energy and metabolites of the brain itself is shallow, which means that the brain is vulnerable to blood flow interference [ 18 ]. Some studies have found that acupuncture for early stroke (12–24 h) can promote the expression of vascular endothelial growth factor (VEGF), which helps to restore oxygen or nutrition supply in the ischemic penumbra [ 19 ]. Acupuncture also provides a beneficial environment for injured tissue, providing a theoretical basis for acupuncture intervention in early stroke [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Excessive glutamic acid can damage neurons and induce extemporaneous toxicity. It not only affects the infarcted area but also damages the CA1 subfield of the hippocampus [ 19 ]. Chen et al found that EA could decrease glutamate release in hippocampal CA1 subfield and inhibit hyperemia during reperfusion [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, tDCS combined with FES gait training improved post-stroke patients' gait regularity better than a FES gait training intervention only (Mitsutake et al, 2021). In the treatment of stroke, some scholars have used our theoretical method (Yu et al, 2020;Yang et al, 2021). There is no best recommendation for CPC therapy.…”
Section: Application Of Central-peripheral-central Closed-loop Rehabi...mentioning
confidence: 99%